Advantages of growth and competitive ability of the invasive plant Solanum rostratum over two co-occurring natives and the effects of nitrogen levels and forms - Sun, Jian-Kun; Liu, Ming-Chao; Tang, Kai-Qi; Tang, En-Xiong; Cong, Jian-Min; Lu, Xiu-Rong; Liu, Zhi-Xiang; Feng, Yu-Long (Frontiers in Plant Science, 2023)
Atmospheric nitrogen (N) deposition has often been considered as a driver of exotic plant invasions. However, most related studies focused on the effects of soil N levels, and few on those of N forms, and few related studies were conducted in the fields. In this study, we grew Solanum rostratum, a notorious invader in arid/semi-arid and barren habitats, and two coexisting native plants Leymus chinensis and Agropyron cristatum in mono- and mixed cultures in the fields in Baicheng, northeast China, and investigated the effects of N levels and forms on the invasiveness of S. rostratum. Compared with the two native plants, S. rostratum had higher aboveground and total biomass in both mono- and mixed monocultures under all N treatments, and higher competitive ability under almost all N treatments. N addition enhanced the growth and competitive advantage of the invader under most conditions, and facilitated invasion success of S. rostratum. The growth and competitive ability of the invader were higher under low nitrate relative to low ammonium treatment. The advantages of the invader were associated with its higher total leaf area and lower root to shoot ratio compared with the two native plants. The invader also had a higher light-saturated photosynthetic rate than the two native plants in mixed culture (not significant under high nitrate condition), but not in monoculture. Our results indicated that N (especially nitrate) deposition may also promote invasion of exotic plants in arid/semi-arid and barren habitats, and the effects of N forms and interspecific competition need to be taken into consideration when studying the effects of N deposition on invasion of exotic plants.